Study of the cation distributions in Eu doped Sr2Y8(SiO4)6O2 by X-ray diffraction and photoluminescent spectra - Shen, Yiqiang (2012)
The crystal structure and photoluminescent properties of europium doped silicate Sr2Y8(SiO4)6O2:Eu3+ are reported. The Sr2Y8−xEux(SiO4)6O2 compounds have typical apatite crystal structures with the P63/m space group. The distributions of Eu3+ between the two crystallographic sites 4f and 6h in the apatite structure are investigated by the powder X-ray diffraction and Rietveld refinement. Results show that Eu3+ ions only occupy the 4f sites when the Eu doping concentration is low (x=0–0.5 in Sr2Y8−xEux(SiO4)6O2). However, in higher concentrations, Eu3+ ions begin to enter the 6h sites as well. The distributions of the Eu3+ are also reflected in photoluminescent spectra. The CIE coordinates for Sr2Y6Eu2(SiO4)6O2 are (0.63, 0.37), which is close to the pure red color.